THE IMPACTS OF FLOODS ON FOOD SECURITY IN HODAN DISTRICT, MOGADISHU-SOMALIA USING A CROSS-SECTIONAL STUDY. - Kampala University , Graduate School; Abdirisak, Isse Aar (Student's Journal of Health Research Africa, 2023)
Background Flood incident affects the source of income and the ability of individuals and households in the communities to purchase and consume food with the daily required energy intake which increases food insecurity, unavailability of staple food, and malnutrition. Flood increases the inability of plants to absorb essential nutrients necessary for proper growth, flooding leads to the erosion or loss of the nutritional status of crops planted in the communities, the washing away of farmlands has led to chronic, long-lasting food insecurity in the communities. Thus, a juxtaposition of Somalia’s poverty level and vulnerability to climate-induced flooding threatens food security in the country. Methodology The study was carried out in Hodan district, Mogadishu- Somalia. A total of 160 persons were targeted. The cross-sectional study design was used for this research. The survey design is preferred because surveys are relatively less costly, easily accessible, and useful in describing the characteristics of a large population and making the results statistically significant even when analyzing the variables. This study used simple random techniques to select samples without bias from the target/accessible population. Results The impact of floods on food security on average is rated to a mean of 3.5 which is relatively high. Conclusion The level of floods that affect food security result indicated that is generally rated very high level by the overall mean (overall mean=3.33) Recommendation The study has been able to demonstrate that flooding induces food insecurity leading to changes in food consumption patterns, and this flood-induced food insecurity arises as a result of the destruction of farmland, disruption of sources of livelihoods, and rise in food prices which significantly affect food availability, accessibility and utilization over time.